O artystycznej i kulturalnej działalności Stowarzyszenia Polskich Muzyków Kameralistów na terenie województwa lubuskiego i nie tylko = On the artistic and cultural activities of the Polish Chamber Musicians` Association (SMPK) in the Lubuskie Voivodeship and beyond - Kataryńczuk-Mania, Lidia; Kuncewicz, Małgorzata; Mania, Grzegorz (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This article highlights the value of organisational work and various artistic, cultural and publishing initiatives, including music festivals, outreach projects, training activities, and academic research (incl. copyright). It also emphasises both domestic and international collaborations, as well as the association`s publishing efforts.
Keywords: Stowarzyszenie Polskich Muzyków Kameralistów (SPMK); muzyka kameralna; popularyzacja muzyki; Polish Chamber Musicians` Association (SPMK); chamber music; music promotion